“Facing both ways” an investigation of the mix of situated knowledge and formal knowledge in boat building - Davidson, Vanessa (School of Education, 2019)
This study looks at vocational curriculum and pedagogy within the context of internal knowledge structures. Focused on a South African boat building qualification, to determine the nature of the qualification and the enacted curriculum with respect to the type of knowledge required in boat building labour processes. In particular the study focuses on the dual demands of innovation and reproduction in a global context. The study attempts to broaden two empirical studies done by Gamble (2004) and Coetzee (2011) into cabinet making and train driving respectively, and an HSRC commissioned study (2015) into artisanal work of the future. The study develops a conceptual framework of the logic of boat building work that meets the dual demands of innovation and reproduction. The conceptual framework develops the hypothesis that different types of knowledge are required to meet the competing demands of ‘innovation’ and ‘reproduction’. To explore the hypothesis, a labour process analysis is undertaken and then the structure and content of the qualification is examined using a coding device re-contextualised from a four-way knowledge schema developed by Gamble (2016a,) as well as an examination of the workshop component of the learnership and the learning material. The study finds that the curriculum attempts to teach in an old craft-based method of apprenticeship. It also finds that the qualification addresses the procedural and sequential requirements of boat building. The problem is that while this addresses the historical craft-based aspects of the trade, it does not support technological innovation. In conclusion, the contribution of this study is to the importance of knowledge in vocational education and, in particular theoretical scientific knowledge and, the role it plays in vocational qualifications and curriculum in a technologically developing world.